The Adventures of Marco Flamingo Under the Sea - Jarkins, Sheila (McHenry, IL : Raven Tree Press, 2009)
Marco Flamingo decides that he wants to visit the open ocean, even though everyone he asks says it is no place for a flamingo, but with the help of some scuba gear he is able to find out for himself, and make some new friends too.
Keywords: Flamingos -- Fiction; Underwater exploration -- Fiction; Marine animals -- Fiction